Regulation of Physical Data on Land Destroyed by Natural Disasters - Anugrah, Dikha; Dialog, Bias Lintang; Akhmaddhian, Suwari; Gustianitami, Azmy Sabila (Universitas Kuningan, 2023)
Natural disaster has a multifaceted impact on the environment, the land, for instance. The demolition of land boundaries and the loss of legal footing ownership are intricate problems surrounding reconstruction. Not to mention the massive losses suffered by citizens as a result of natural disasters that exacerbate the situation. The study employed a socio-legal method, referring to library sources such as books, journals, statutory regulations, and literature reviews. According to the findings, tangible data on destroyed land caused by natural disaster is fairly organised. Furthermore, the legal position of land rights affected by an earthquake is not removed; nonetheless, the abrasion-caused is discarded. Accordingly, the government, notably the National Land Agency, should create regulations that control and streamline the procedure for victims who have lost their civil rights, land boundaries, or disasters that have been lost or cannot be recognised.